PENGARUH MASALAH KELUARGA TERHADAP KESEHATAN MENTAL REMAJA - Zakia Rahmadania; Hana Pratiwi; Risma Anita Puriani (CV. Adiba Aisha Amira, 2026)
This research aims to examine the influence of family problems on the mental health of adolescents using a literature review approach. This study analyzes 20 scientific articles published in the last five years to identify various family factors that influence the psychological condition of adolescents. The analysis results show that family problems have a strong relationship with the mental health of adolescents. Several influencing factors include inadequate economic conditions, parental divorce (broken home), ineffective family communication, inappropriate parenting styles, disharmonious family relationships, and minimal emotional support, all of which contribute to an increased risk of psychological disorders such as stress, anxiety, and depression. On the other hand, families that can provide emotional support, build good communication, and implement positive and supportive parenting styles can be protective factors that strengthen the resilience and mental well-being of adolescents. Therefore, the family can be considered the main factor influencing the psychological condition of adolescents compared to other environmental factors.